Corporate Finance and Monetary Policy - Rocheteau, Guillaume; Wright, Randall; Zhang, Cathy (American Economic Review, 2018)
We develop a general equilibrium model where entrepreneurs finance random investment opportunities using trade credit, bank-issued assets, or currency. They search for bank funding in over-the-counter markets where loan sizes, interest rates, and down payments are negotiated bilaterally. The theory generates pass-through from nominal interest rates to real lending rates depending on market microstructure, policy, and firm characteristics. Higher banks' bargaining power, for example, raises pass-through but weakens transmission to investment. Interest rate spreads arise from liquidity, regulatory, and intermediation premia and depend on policy described as money growth or open market operations. (JEL E43, E52, G21, G31, G32, L26)